PENGARUH TIDAK LANGSUNG INTELLECTUAL CAPITAL TERHADAP PENCIPTAAN NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE - Debra Yulita Perwira; Agung Juliarto (Diponegoro Journal of Accounting, 2015)
This study aims to examine the indirect effects of intellectual capital and its components in value creation of property and real estate companies, which have characteristic that intensive of tangible asset. The independent variable is intellectual capital that measured by using Value Added Intellectual Coefficient (VAIC). The dependent variable that used in this study is the market value proxied by market-to-book ratio. Indirect effect testing is done by including financial performance measured using ROIC. The population in this study was property and real estate companies listed on the Indonesian Stock Exchange (BEI) in 2009-2013. Sampling method was used as purposive sampling. Sample comprised with total observation were 195 companies for 5 years. Data were analyzed by using path analysis with smartPLS software version 2. The results of this study show that intellectual capital influence on financial performance significantly. Financial performance also influence on the market value significantly. This study is able to prove that intellectual capital indirectly influence firms value through the financial perfomance. Overall, result of this study indicates that the relationship between intellectual capital and value of the property and real estate companies is indirect.